The Biopesticide Landscape in India: Current Status - R. Venkat Ramchandar (The Bioscan, 2026)
India's biopesticides market is changing quickly due to shifting consumer preferences, growing international agricultural commerce, and shifting regulations. Currently, 5% of India's pesticide market is made up of biopesticides. The biopesticides market in India is expected to grow at a 9.5% compound annual growth rate (CAGR) from its estimated value of USD 242.16 million in 2025 to USD 381.23 million by 2030. There are 970 bio registrants in India with 28 different biopesticides. These include (a) microbial biopesticides such as (i) entomopathogenic fungi biopesticides (ii) antagonistic bacteria biopesticides (iii) antagonistic fungi biopesticides (iv) entomotoxic bacteria biopesticides and (v) baculo virus biopesticides and (b) botanical biopesticides under (i) eucalyptus extract containing eucalyptol biopesticides,(ii) rotenone containing biopesticides for pisciculture (iii) Cymbopogon extract containing biopesticides (iv) pyrethrum extract containing biopesticides (v) herbal plant growth regulators (vi) Neem based products containing azadirachtin for house hold uses biopesticides (vii) Neem based products as biopesticides etc. Because of their generally lower environmental impact and ability to promote ecological balance, biopesticides are widely considered a sustainable non- conventional alternative or supplement to conventional chemical pesticides. They offer unique advantages that address several problems associated with synthetic substances. Biopesticides are the cornerstone of integrated pest management (IPM) strategies because, in contrast to chemical pesticides, they degrade quickly in the environment and may not last longer (reduced environmental persistence), are highly specific to target pests, preserve biodiversity without harming nontarget pests, and pose little to no risk to humans and animals.